Doctors’ Perceptions, Attitudes and Practices towards the Management of Multidrug-Resistant Organism Infections after the Implementation of an Antimicrobial Stewardship Programme during the COVID-19 Pandemic - Nikolaos Spernovasilis; Despo Ierodiakonou; Christos Spanias; Anna Mathioudaki; Petros Ioannou; Emmanouil C. Petrakis; Diamantis P. Kofteridis (Tropical Medicine and Infectious Disease, 2021)
Background: Greece is among the European countries with the highest consumption of antibiotics, both in community and hospital settings, including last-line antibiotics, such as carbapenems. We sought to explore doctors’ perceptions, attitudes and practices towards the management of patients with multidrug-resistant organism (MDRO) infections after the implementation of an antimicrobial stewardship programme (ASP) in a tertiary academic hospital during the COVID-19 pandemic. Methods: A self-administered, internet-based questionnaire survey was completed by doctors of the University Hospital of Heraklion in Crete, Greece. Results: In total, 202 (59.1%) hospital doctors fully completed the questionnaire. Most of them agreed that the prospective audit and feedback ASP strategy is more effective and educational than the preauthorization ASP strategy. ASP implementation prompted most respondents to monitor the continuously evolving microbiological data of their patients more closely and affected them towards a multidisciplinary and personalised care of patients with infections caused by MDROs and towards a more rigorous implementation of infection prevention and control measures. The vast majority of participants (98.5%) stated that ASP must be continued and further developed during the COVID-19 pandemic. Conclusion: The ASP implementation in our hospital had a beneficial impact on doctors’ perceptions, attitudes and practices with regard to the management of infections due to MDROs.